2020
DOI: 10.1177/0194599820937991
|View full text |Cite
|
Sign up to set email alerts
|

Vasodilation by Verapamil‐Nitroglycerin Solution in Microvascular Surgery

Abstract: Objective Papaverine is a topical vasodilator commonly used during microvascular surgery to inhibit undesired vasoconstriction. A previous national shortage of papaverine prompted evaluation of an alternative, effective vasodilator. This study aims to assess the experience of a solution of verapamil and nitroglycerin (VG) as a potential alternative pharmacologic vasodilator. Study Design Retrospective case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Yu et al 25 found that 94% of microvascular surgeons implement topical vasodilators with the most common agents being papaverine, verapamil, and lidocaine. Papaverine is a phosphodiesterase inhibitor and acts as a smooth muscle relaxant via an incompletely known mechanism involving direct action on calcium channels along with increases in cyclic guanosine monophosphate (cGMP) 23,26 . In vitro studies have demonstrated up to 60% increase in vessel caliber with papaverine treatment 27 .…”
Section: Topical Vasodilatorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Yu et al 25 found that 94% of microvascular surgeons implement topical vasodilators with the most common agents being papaverine, verapamil, and lidocaine. Papaverine is a phosphodiesterase inhibitor and acts as a smooth muscle relaxant via an incompletely known mechanism involving direct action on calcium channels along with increases in cyclic guanosine monophosphate (cGMP) 23,26 . In vitro studies have demonstrated up to 60% increase in vessel caliber with papaverine treatment 27 .…”
Section: Topical Vasodilatorsmentioning
confidence: 99%
“…At low concentrations (2%) lidocaine may induce norepinephrine‐mediated vasoconstriction while vasodilatory effects are seen at higher concentrations (20%) 28 . However, its use is limited by the risk of systemic toxicity with high dose lidocaine and thus it is less regularly implemented than papaverine or verapamil 23 . Lastly, topical nitroglycerin has been implemented at some centers in the setting of recent papaverine national shortages 23,26 .…”
Section: Topical Vasodilatorsmentioning
confidence: 99%
See 3 more Smart Citations